Estudio del autocontrol emocional de un adolescente con problemas de comportamiento y propuesta de intervención desde las artes plásticas - Arroyo Acero, Karina Fernanda; Díaz Mosquera, Elena (Revista Ecos de la Academia, 2021)
This research mentions different studies of the plastics arts, in the painting and sculpture disciplines. The goal is to analyze the way in which the plastics arts strengthen the emotional self-control of an adolescent who presents behavioral problems, the research was developed from a qualitative approach. To measure self-control, three instruments were used: an interview to parents, an interview to the adolescent and an observation sheet, whose indicators were taken and adapted from DSM V, specifically for Defiant Negative Disorder. In the study case was found, symptoms associated with a low level of emotional self-control in adolescents. From the starting point of the specific objectives, is also done a bibliography research of the benefits of painting and sculpture although no work related to emotional self-control was found, studies were found on the benefits of art associated with other psychological and health difficulties. In this framework, it is concluded that the practice of painting and sculpture contributes to a large extent to the proper management of emotions in a person. Finally, it is proposed an Intervention Plan for the adolescent of the case study, focused from the plastic arts.